Cost-Effectiveness of Optimal Use of Acute Myocardial Infarction Treatments and Impact on Coronary Heart Disease Mortality in China - Wang, Miao (2014)
BACKGROUND: The cost-effectiveness of the optimal use of hospital-based acute myocardial infarction (AMI) treatments and their potential impact on coronary heart disease (CHD) mortality in China is not well known. METHODS AND RESULTS: The effectiveness and costs of optimal use of hospital-based AMI treatments were estimated by the CHD Policy Model-China, a Markov-style computer simulation model. Changes in simulated AMI, CHD mortality, quality-adjusted life years, and total healthcare costs were the outcomes. The incremental cost-effectiveness ratio was used to assess projected cost-effectiveness. Optimal use of 4 oral drugs (aspirin, β-blockers, statins, and angiotensin-converting enzyme inhibitors) in all eligible patients with AMI or unfractionated heparin in non–ST-segment–elevation myocardial infarction was a highly cost-effective strategy (incremental cost-effectiveness ratios approximately US $3100 or less). Optimal use of reperfusion therapies in eligible patients with ST-segment–elevation myocardial infarction was moderately cost effective (incremental cost-effectiveness ratio ≤$10 700). Optimal use of clopidogrel for all eligible patients with AMI or primary percutaneous coronary intervention among high-risk patients with non–ST-segment– elevation myocardial infarction in tertiary hospitals alone was less cost effective. Use of all the selected hospital-based AMI treatment strategies together would be cost-effective and reduce the total CHD mortality rate in China by ≈9.6%. CONCLUSIONS: Optimal use of most standard hospital-based AMI treatment strategies, especially combined strategies, would be cost effective in China. However, because so many AMI deaths occur outside of the hospital in China, the overall impact on preventing CHD deaths was projected to be modest.